Design of a novel optimal control based on non-conventional prescribed performance boundaries for vibration control and its application to vehicle seat suspension with a semi-active MR damper - Thi Truc Thao Phan; Xuan Phu Do; Seung Bok Choi; Huy Tuan Pham (Advances in Mechanical Engineering)
This study presents a novel optimal controller that is designed based on a linear transformation with upper and lower prescribed functions. The utilization of the linear transformation, akin to the Kalman function, forms an integral part of the optimal control input. The development of the proposed controller is rooted in non-conventional prescribed techniques, which contribute to its uniqueness and innovative nature. The effectiveness of the proposed controllers is assessed by applying them to regulate the vibration of a suspension system featuring a semi-active magnetorheological fluid base damper (MR Damper in short). Initially, random peaks representing random disturbances are employed as excitations in the simulation and two benchmark controllers (conventional optimal control and linear matrix inequality (LMI) control which has been modified to have conventional upper and lower boundaries) are carefully selected for reasonable comparison. The simulation results unequivocally demonstrate that the proposed controller possesses stronger capabilities in suppressing vibrations when compared to the benchmark controllers. The controllers are also applied in the real suspension system. The experimental results show that the proposed control provides better than the comparative controllers with around 18% and 35% reduction for the seat displacement and the seat acceleration, respectively.